Pathophysiological Changes in Erythrocytes Contributing to Complications of Inflammation and Coagulation in COVID-19 - Soma, Prashilla; Bester, Janette (Frontiers in Physiology, 2022)
Higher thrombotic burden in the acute phase of COVID-19 relies on a complex interplay between pro-inflammatory cytokine/chemokine release, increased endothelial dysfunction/damage, and potential sepsis-induced coagulopathy development in severe cases, all promoting coagulation activation. Plasma levels of cytokines and chemokines are known to be increased in COVID-19 however, are much higher in severe infections. Increased levels of IL-1β, IL-6, and IL-8 are known to play an important role in both acute and chronic inflammation, with resulting pathological clotting. However, little has been published on the effects of these interleukins on red blood cells (RBCs). Evidence shows that increased levels of IL-8 have a negative effect on the RBCs ultrastructure and introduce signs of eryptosis. Eryptosis can be described as a form of suicidal death of RBCs characterized by distinct findings of cell shrinkage, membrane blebbing, activation of proteases, and phosphatidylserine exposure at the outer membrane leaflet. Red blood cells from COVID-19 patients had increased levels of glycolytic intermediates, accompanied by oxidation and fragmentation of ankyrin, spectrin beta, and the N-terminal cytosolic domain of band 3 (AE1). Significantly altered lipid metabolism was also observed, in particular, short- and medium-chain saturated fatty acids, acyl-carnitines, and sphingolipids. Emerging research suggests that RBCs may contribute to a precision medicine approach to sepsis and have diagnostic value in monitoring complement dysregulation in COVID-19-sepsis and non-COVID sepsis as research indicates that complement activation products and viral antigens are present on RBCs in patients with COVID-19.